CASE REPORTSPotts’ shunt in a child with idiopathic pulmonary arterial hypertension – one-and-a-half year observation - Fiszer, Roland; Karwot, Blandyna; Chodór, Beata; Szkutnik, Małgorzata; Kobylarz, Krzysztof; Skalski, Janusz; Białkowski, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
This paper presents the case of a young girl with idiopathic pulmonary hypertension, who developed signs of severe heart failure within a short period of time. Pharmacotherapy with sildenafil and bosentan (among other drugs) was ineffective. Heart catheterization revealed suprasystemic pressure in the pulmonary artery. At the age of 7.5 years, the patient underwent a surgical Potts shunt (namely, a direct side-by-side anastomosis from the left pulmonary artery to the descending aorta). The procedure resulted in a significant improvement of the clinical, echocardiographic, and biochemical parameters, which persists after one and a half years of follow-up. After the surgery, pharmacotherapy with bosentan was gradually discontinued.